Entre a Expansão e o Declínio: A Democratização do Acesso ao Ensino Superior e a Queda nas Inscrições do Enem no Período 2017- 2021 - Reses, Erlando Silva; Carvalho, Bruno Moreira Borges (Latitude, 2025)
At a time when the update of affirmative action policies in public universities is being consolidated and we mark the 25th anniversary of the creation of the National High School Exam (ENEM), this article aims to analyze the recent decrease in the number of applicants in the main mode of entry into the country's public universities, as well as to present the contribution of the intersectional perspective to understanding this phenomenon. The foundation of this work is based on data released by the National Institute for Educational Studies and Research Anísio Teixeira (INEP) and the Ministry of Education, highlighting the ENEM Microdata, the Higher Education Census, and the ENEM Press Kits (INEP). The research underscores the centrality of the exam in the process of democratizing access to Brazilian higher education and identifies the possible explanatory factors for the reduction in the number of applicants from 2017 to 2021.